Forest recovering and soil respiration rate - Mande, Hosea Kato; Abdullah, Ahmad Makmom; Nuruddin, Ahmad Ainuddin; Bose, Mahmud Mohammad; Binyehmed, Fadel Mohamed; Ben Youssef, Khaleed Ali Ahmed; Emmanuel, Gabriel (International Organization of Scientific Research, 2014)
This study was conducted to investigate the rate of soil respiration from a recovering forest of the tropics and its relationship with changes in environmental factorsafter years of deforestation. Soil respiration measurement was conducted using the continuous open flow chamber technique connected to a multi gas-handling unit and infrared gas analyser, while the forest biomass and soil properties were quantified using the Kjeldahl method and Walkley-black wet oxidation technique. The average means soil respiration rate were 341.23, 383.07, 340.30, 308.12, 286.07, 256.05 mg m-2 h-1 between June and December. Soil respiration in the month of July was significantly (p<0.01) higher compare to other months, with lower emission rate in December. Soil respiration exhibited a variation pattern that was similar to soil temperature pattern, the pattern varied monthly.